A Multi-dimensional framework for adopting Physical Address System in a developing country - Ditsela, Jeofrey (My University, 2017)
This thesis is about the adoption of an Information System (IS) at a country level. Information Systems literature addresses adoption of IS at an individual level, organisational level or national/country level. Each level of analysis has its own complexities. However, literature acknowledging these varied complexities has not been forth coming. That is, literature has more studies done at either individual or organisational, and hardly at national or country level. This thesis argues that the adoption of an information system (also referred to as an innovation) at country level is a multi-dimensional and multi-level phenomenon. Existing literature and previous studies have hardily addressed fully, this complexities and multi-dimensionalism, although it has been noted that countries experience and internalise the innovation adoption, as a social process, differently. The study was on a developing country adopting a Physical Address System (PAS), herein seen as an IS innovation. In this thesis, PAS is seen as a social system comprising of artefacts (digital and visual representations), physical world, residents and organisations as stakeholders. The goal of the study was to conceptualise a multi-dimensional framework for adopting a Physical Address System, in the context of a developing country. Since the thesis argument is that the adoption of IS at a country level is even more complex, varied theories were employed as lenses to tackle the various aspect of the study. These lenses are the Diffusion of Innovation, the Stakeholder Theory, Upper Echelon Theory and the Contextualist Approach. Following the interpretivist philosophy, a case study was employed as a research strategy, using Botswana as a developing country case. The research design included semi-structured interviews with stakeholders, observations, policy documents. The data was analysed, discussed, synthesised and interpreted using thematic framework analysis method. Informed by the empirical evidence and the existing literature, this thesis conceptualises that the adoption of the Physical Address System ought to be done sensitive to the developing country as a multi-dimensional social system. This multi-dimensional social system includes the roles of stakeholders, determinants of innovation and context. The contribution of the thesis is in four folds; theoretical, methodological, practical, and contextual. Theoretically, the thesis conceptualised a multi-dimensional framework for the adoption of the Physical Address System in a developing country. Methodologically, the thesis contributed by following an interpretive philosophy and a case study as appropriate for understanding the complexities of adopting an information system, employing a case. Practically, the thesis, through the framework, may inform practitioners with ways to adopt a physical address system. Contextually, the thesis gives insight into the uniqueness of a developing country adopting an information system. Keywords: Developing Country, Adoption, Physical Address System, Stakeholder Theory, Upper Echelon Theory, Diffusion of Innovation, Context
A Doctoral thesis submitted in fulfilment of the requirement for the degree of Doctor of Philosophy in Information Systems, Division of Information Systems School of Economic and Business Sciences Faculty of Commerce, Law and Management.Johannesburg, March 2017
Keywords: Developing Country; Adoption; Physical Address System; Stakeholder Theory; Diffusion of Innovation; Upper Echelon Theory; Management information systems--Developing countries; Diffusion of innovations--Developing countries